Perspektif Perempuan Dalam Film Mimi Melalui Analisis Wacana Kritis Sara Mills - Dionisius Lesmana; Gabriella Monique Valentina (Communicology: Jurnal Ilmu Komunikasi, 2022)
Individual authority can affect the power of other individuals over themselves based on knowledge and experience in society, especially women from marginalized groups in India who are depicted in the Mimi movie which tells the story of a surrogate mother who experiences injustice. The phenomenon against women from marginalized groups is still a long scourge so that an elaboration and understanding of it is needed to solve the occurred problem. The objective of this research is to describe the perspective of women in the Mimi movie through Sara Mills' Critical Discourse Analysis. This research uses a qualitative method through Sara Mills' Critical Discourse Analysis based on the subject, object, and audience’s position. The results of the study show a standpoint that associates the relations of the uppe class society as "masters" and women from the marginalized group as "slaves" who often experience injustice, bullying, harassment, manipulation, and threats. The situated knowledge concept lies in placing women as people who are exploited as commodities. The sexual division of labor concept limits women's potential to have a career according to their expectations and live life in society with the role as a mother who gives birth and take care of her children.